2008
DOI: 10.1093/jn/138.4.768
|View full text |Cite|
|
Sign up to set email alerts
|

Regular Users of Supermarkets in Greater Tunis Have a Slightly Improved Diet Quality3

Abstract: Despite the recent and rapid expansion of supermarkets in developing countries, their association with diet quality has been hardly studied. The study took place in Tunisia, where incidences of obesity and nutrition-related diseases are rising. The target population was households of the Greater Tunis area where supermarkets are mostly located. Households (n = 724) were selected by a 2-stage clustered random sampling. A purposely developed quantitative questionnaire assessed food retail habits. Socioeconomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 24 publications
2
48
1
Order By: Relevance
“…The two studies which the authors have identified which pursue a similar analysis have been carried out in Tunisia and Guatemala (Asfaw, 2008;Tessier et al, 2008). These studies reported conflicting findings with the Tunisian research reporting that regular supermarket shopping was associated with a slight improvement in overall dietary quality, while the Guatemalan study found that purchasing more of food at a supermarket was associated with increased intake of highly and partially processed foods and a higher BMI.…”
mentioning
confidence: 97%
“…The two studies which the authors have identified which pursue a similar analysis have been carried out in Tunisia and Guatemala (Asfaw, 2008;Tessier et al, 2008). These studies reported conflicting findings with the Tunisian research reporting that regular supermarket shopping was associated with a slight improvement in overall dietary quality, while the Guatemalan study found that purchasing more of food at a supermarket was associated with increased intake of highly and partially processed foods and a higher BMI.…”
mentioning
confidence: 97%
“…Several studies suggest that the spread of supermarkets leads to dietary changes for urban consumers (12,(15)(16)(17) . Most of this work shows that supermarket purchase is associated with increased consumption of energy-dense, processed foods (12,15,16) , although in one case supermarkets were found to increase dietary quality (17) . Research on the impact of supermarkets on consumer nutritional status in developing countries is rare.…”
mentioning
confidence: 99%
“…A few studies have also shown that the spread of supermarkets may contribute to improved dietary quality and diversity in poor population segments (Tessier et al, 2008;Rischke et al, 2014). Even when the share of processed foods is increasing, a larger variety of foods may improve micronutrient supply, which is closely associated with child growth.…”
mentioning
confidence: 99%